Pendidikan dan kelembagaan pada masa Turki Utsmani serta relevansinya dengan zaman sekarang - Nasir, Muhammad; Bukhori, Imam (Maliki Interdisciplinary Journal, 2024)
The Ottoman Empire was a large sultanate that was famous for its formidable military strength. This research aims to review the educational situation and institutions that developed during the Ottoman Empire. This research uses a descriptive qualitative research method with a literature study type of research as well as a philosophical and historical approach. The results of this research are that the development of education in the Ottoman Empire began to be noticed during the time of Sultan Ahmad III (1703 – 1730). The peak of the educational reform of the Ottoman Empire occurred during the time of Sultan Mahmud II (1808 – 1839). Educational institutions during the Ottoman era were divided into three levels, namely madrasas, primary education and high schools. Apart from that, there is also a library and a translation bureau.